Is LTFRB Uber-Reacting? - Mendoza, Ronald U (Archīum Ateneo, 2015)
This paper elaborates on the economics of the taxi sector in the Philippines, and the impact of emerging competition such as Uber. It argues that a better understanding of the economics of the taxi industry could help inform regulators on whether and to what extent they should regulate Uber in order to promote the general welfare of the riding public. Uber offers alternatives and could actually be tempering behavior by unfair taxi operators by enhancing competition.